Past, Present, and Future Challenges of the National Museum of the American Indian - Champagne, Duane (2011)
Seven leading thinkers on the presentation of Native American history and contemporary cultures discuss how the essential ideas behind the creation of the National Museum of the American Indian initially were implemented and potentially could evolve. In addition to honoring the leadership and contributions of the museum’s founding director, W. Richard West, Jr., the authors explore such topics as repatriation, the representation of Native voices in exhibitions and programs, and the museum’s ongoing effort to develop its intellectual authority. Synthesizing the papers presented at a symposium of the same name hosted by the museum in October 2007, Past, Present, and Future takes a candid look at the National Museum of the American Indian’s complex genesis and future challenges.